2016
DOI: 10.1161/circresaha.115.307521
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Growth Differentiation Factor 11/8 Levels Decline With Age

Abstract: Rationale Growth differentiation factor 11 (GDF11) and GDF8 are members of the transforming growth factor-β superfamily sharing 89% protein sequence homology. We have previously shown that circulating GDF11 levels decrease with age in mice. However, a recent study by Egerman et al reported that GDF11/8 levels increase with age in mouse serum. Objective Here, we clarify the direction of change of circulating GDF11/8 levels with age and investigate the effects of GDF11 administration on the murine heart. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
220
4
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(243 citation statements)
references
References 19 publications
12
220
4
7
Order By: Relevance
“…significant dose-dependent decrease of heart weight, normalized to tibia length, after only 9 days of treatment in mice receiving 0.5 or 1.0 mg/kg/day GDF11. 9 In this study, we found that GDF11 improved endothelial dysfunction, decreased endothelial apoptosis in vivo and in vitro, and reduced atherosclerosis plaque including the en face and cross section areas as well as enhanced mature plaque stability in apoE −/− mice. Moreover, our human study showed that circulating GDF11/8 levels are positively associated with FMD in male overweight subjects.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…significant dose-dependent decrease of heart weight, normalized to tibia length, after only 9 days of treatment in mice receiving 0.5 or 1.0 mg/kg/day GDF11. 9 In this study, we found that GDF11 improved endothelial dysfunction, decreased endothelial apoptosis in vivo and in vitro, and reduced atherosclerosis plaque including the en face and cross section areas as well as enhanced mature plaque stability in apoE −/− mice. Moreover, our human study showed that circulating GDF11/8 levels are positively associated with FMD in male overweight subjects.…”
Section: Discussionmentioning
confidence: 52%
“…However, other data showed that the increase of serum GDF11 in mice reported by Egerman et al is not GDF11 but predominantly immunoglobulin light chain (the ~25 kDa band by Western blot), immunoglobulins have long been known to increase with age in C57BL/6 mice. 9 They also found that circulating GDF11/8 levels decline with age in multiple mammalian species. In this study, we also found circulating GDF11/8 levels decline with age in mice and in male overweight subjects.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The interaction of propeptide and myostatin is relevant in vivo, with a majority (Ͼ70%) of myostatin in serum bound to its propeptide (16). The amino acid sequence of GDF-11 (growth/differentiation factor-11) is 90% homologous to myostatin in the carboxy-terminal mature region of the protein, and like myostatin, GDF-11 can signal through ActRIIB (30), and GDF-11 administration leads to activation of Smad2 signaling (12,34). Myostatin propeptide may bind and inhibit GDF-11 as well as myostatin (30); therefore, the mutant propeptide of Compact mice might disturb not only myostatin but, e.g., GDF-11 signaling as well.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed histological analysis showed that the myostatin KO (knock out) mice exhibit increased ratio of fast glycolytic, type IIB fibers with a concomitant decrease in oxidative type IIA and type I fibers in tibialis anterior and biceps femoris muscles [33]. Notably, this increased muscle mass is not accompanied by the proportionate increase in specific muscle force [34].…”
Section: Major Characteristics Of the Myostatin Knock Out Micementioning
confidence: 99%